TBIO-03. THE GIFT FROM A CHILD PROGRAM IS EMPOWERING POST-MORTEM TISSUE DONATION ACROSS THE UNITED STATES. (4th December 2020) - Waanders, Angela; Williams, Melissa; Wadwhani, Nitin; Li, Xiao-Nan; Goldman, Stewart; Tran-Du, Kella; Minturn, Jane; Mason, Jennifer; Santi, Mariarita; Viaene, Angela; Koptyra, Mateusz; Monje-Deisseroth, Michelle; et al.
Abstract: The Gift from a Child (GFAC) program was inspired by the dream of one child to donate his brain for research, recognizing the need to study tumor tissue collected at diagnosis, recurrence, and at the time of death. Founded by the Swifty Foundation in 2016, GFAC currently is comprised of five "Centers of Excellence" at institutions with expertise in pediatric neuro-oncology. Partnering with the Children's Brain Tumor Network, the program's mandate is twofold: make it possible for families to donate no matter where they live in the United States and make tissue available to scientists globally to empower discovery. In order to overcome barriers that have stifled postmortem collection in the past, GFAC has invested in Tissue Navigators - individuals at each center who coordinate all aspects of donation and communicate with families, medical providers, and laboratory scientists. In 2019 alone, GFAC coordinated 55 autopsy collections from multiple diagnosis. A key metric of the program is also capturing the global sharing and usage of each tissue sample, ensuring that tissue isn't simply "banked" but is actively being actively used to help unravel tumor biology. To date, tissue has been used for genomic and molecular data generation, preclinical model development including cell lines and PDX models, and for novel drug screening. Together with Children's Brain Tumor Network, the Gift from a Child program is helping to ensure the most precious gift that a family can make is used to accelerate the path to cures.